The University Professor View from the Communitarian Perspective - Valle López, Angela del (2014)
The task of the university professor is a mission and not simply a profession and that is why higher education should be impregnated with values. Nowadays education is articulated into three areas: the State, the Market and the Volunteering, but no one of these three sectors by themselves has covered the needs of all the citizens, there have always been losers, therefore the conjunction of the three sectors became necessary. Communitarianism promotes an ethical-social pact that favors the progress of society without nullifying the individual dimension. It believes that the university is the space where a communitarian consciousness should be promoted to generate a social capital by means of education and it is a privilege place to substantiate the moral identity of the person beginning with the commitment of the professor with the university student.